Asymmetric Synthesis of Benzothiophene-Containing Lipoxin A4 Analogues with Lower-Chain Modifications - Tighe, Catherine; Owen, Benjamin; Guiry, Patrick J. (Synthesis, 2023)
Lipoxins are an important class of pro-resolving mediators that play a crucial role in the resolution of inflammation. Thus, the synthesis of more metabolically stable synthetic lipoxin analogues is an area of significant interest. Herein the asymmetric synthesis of lipoxin A4 (LXA4) mimetics is reported in which the triene core of the molecule has been replaced by an aromatic sulfur-containing benzothiophene ring. The key steps in the synthesis included a Friedel–Crafts acylation, a Suzuki coupling between two upper and lower chain fragments, and a highly stereoselective Noyori transfer hydrogenation to set the stereochemistry of the alcohol at the benzylic position. A small library of benzothiophene-containing LXA4 analogues with further structural modifications was also successfully synthesised. These included analogues with phenoxy, p-fluorophenoxy, and p-trifluoromethylphenoxy substituents incorporated into the lower alkyl chain with the objective of providing enhanced metabolic stability by blocking ω-oxidation pathways.
Keywords: lipoxin A4; benzothiophene; asymmetric synthesis; anti-inflammatory; medicinal chemistry